A new method for estimating parameters of a dynamic robot model. - Olsen, M.M (IEEE Transactions on robotics and automation)
The need for open model-based robot controllers becomes more and more important with the increasing quality of autonomous joint motion planners and the increasing amount of applications for these. An important item in a model-based controller is a precise dynamical model of the robot. Such a model is designed in terms of various inertial and friction parameters that must be either measured directly or determined experimentally. In this paper, we present a new method for determining parameters of a dynamical robot model based on experiments. We compare the method with existing methods both theoretically and experimentally, and show that we achieved some improvements in the parameter values by using the new method. The experiments were carried out on the two first links of a seven-axis Mitsubishi PA-10 robot